Study of the variability of the precipitation and temperature in the Quindio River basin (Revista de Investigaciones Universidad del Quindío, 2009)
The difficulties in regard to water quality and quantity make clear that to 2025, 41% of the population will not count with water availability for assumption, and that, the main aquatic source, the Quindio River, has compromised the 80.4% of its production. The fossil fuels burning increases the green house gasses concentration in the atmosphere. It is estimated that these alterations will change the regional and global climate, and so the parameters related to it. The main objective of the study was to establish a perspective of the climate variable tendencies in the Quindio River Basin, by selecting stations that contain records of temperature and precipitation as the climatic elements that describe the best the water comportment in the atmospheric component. It is proposed to identify the comportment of the selected variables by means of the construction of ARIMA models, using Box and Jenkins' (1976) methodology. The precipitation series do not show any tendency type, they exhibit variations that could be assumed as stationary on their regular part, the best adjust model was an ARIMA (1,0,0)(2,1,0)12. The temperature series showed strong growth tendencies and the presence of atypical periods that are related with anomalous climatic events, the best adjust model was an ARIMA (3,1,0)(1,1,0)12.
Keywords: Climate Change; Hydrology; ARIMA Models